Summer school on intelligent agents in automation: Experience and reflections from the second edition - Ribeiro, Luis (2018)
Several research agendas worldwide are targeting the development of Industrial Cyber-physical Systems as the next generation of intelligent embedded devices with improved interaction capabilities. These devices, and their potential uses, are though to deliver a radical increase in system sustainability, reconfigurability and flexibility which is perceived to be the root of the so called 4 th Industrial Revolution. However such technical systems, at the envisioned revolutionary scale, do not exist just yet and require a convergent and multidisciplinary research and development efforts. The academia curricula are also, albeit slowly, adjusting to the emerging education requirements. The Summer School on Intelligent Agents in Automation is a joint effort from several researchers in core areas of the 4 th Industrial Revolution landscape to close the gap and promote advanced education in this context. This paper describes the implementation of the 2 nd edition of the event as well as the experience and reflections resultant from it.